Inovasi Diferensiasi Produk dengan Metode Alih Wahana pada Materi Teks Laporan Hasil Observasi - Muhammad Kriswanto; Nanang Bustanul Fauzi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Product differentiation is learning based on multiple approaches to assignments given to students. It gives students the freedom to develop the understanding and competencies they are interested in. The existence of different learning tools in the Merdeka curriculum is the goal of achieving understanding and developing competence. This study focuses on describing the concept of differentiation learning to accommodate differences in student learning styles and describes product differentiation innovations on ‘alih wahana’ learning of observation report text. This study used a qualitative approach and a literature review design. The data are in quotations, theories, and paradigms describing the studied problems. Data was collected using reading and note-taking techniques and processed using analytical techniques in the form of (a) data presentation; (b) data reduction; (c) data interpretation; and (d) conclusion. The results of this study are, first, learning differentiation as a learning strategy. This strategy targets a variety of student learning styles through content, processes, and products according to characteristics to achieve goals. Second, product differentiation can be designed using the ‘alih wahana’ method in observation reports text material in the form of informative video media, infographics, and scrapbooks.